DFT study of the interaction between carbon monoxide and Rh-Cu bimetallic nanoclusters. (March 2021) - Arab, Ali
Graphical abstract: Highlights: Chemisorption of CO on the clusters along with the formation of chemical bond(s) was observed. CO binds stronger to Rh-Cu bimetallic clusters compared to the pure Cu4 cluster. The cluster CO bonds arise mainly from the cluster→(CO) π-back-donation. Abstract: The interaction between CO and Rhx Cu4-x (x = 0–4) nanoclusters was studied using B3PW91 hybrid functional. The values of adsorption energies for the most stable structures that were in the range between −1.25 eV to -2.41 eV indicated chemisorption of CO on the clusters along with the formation of chemical bond(s). The nature of these chemical bonds was investigated by NBO analysis and calculation of Wiberg bond indexes as well as considering the change in CO bond length and frequency. It was concluded that the cluster−CO bonds arose mainly from the cluster→(CO) π-back-donation. Also, the NBO analyses revealed that for the adsorption of CO in the bridge and on the top sites, availability of d orbitals and s&p orbitals of cluster atoms was required respectively. Therefore, on the one hand for RhCu3 and Cu4 clusters adsorption in the bridge site was not observed because of the fully occupied d orbitals of Cu atoms but for Rh4, Rh3 Cu, and Rh2 Cu2 clusters, on the other hand, the adsorption in the bridge of two Rh atoms was the most stable structure. More favorable adsorption on Rh-Cu bimetallic clusters compared to pure Cu4 cluster was also observed.